A Comparison of Computation Span and Reading Span Working Memory Measures' Relations With Problem-Solving Criteria. Issue 3 (June 2018) - Perlow, Richard; Jattuso, Mia
Researchers have operationalized working memory in different ways and although working memory–performance relationships are well documented, there has been relatively less attention devoted to determining whether seemingly similar measures yield comparable relations with performance outcomes. Our objective is to assess whether two working memory measures deploying the same processes but different item content yield different relations with two problem-solving criteria. Participants completed a computation-based working memory measure and a reading-based measure prior to performing a computerized simulation. Results reveal differential relations with one of the two criteria and support the notion that the two working memory measures tap working memory capacity and other cognitive abilities. One implication for theory development is that researchers should consider incorporating other cognitive abilities in their working memory models and that the selection of those abilities should correspond to the criterion of interest. One practical implication is that researchers and practitioners shouldn't automatically assume that different phonological loop-based working memory scales are interchangeable.